2023
DOI: 10.3390/metabo13020306
|View full text |Cite
|
Sign up to set email alerts
|

Hypomagnesemia as a Risk Factor and Accelerator for Vascular Aging in Diabetes Mellitus and Chronic Kidney Disease

Abstract: The age-old axiom that one is as old as his or her vessels are, calls for ongoing critical re-examination of modifiable risk factors of accelerated vascular ageing in chronic kidney diseases. Attempts to modulate vascular risk with cholesterol-lowering agents have largely failed in advanced chronic kidney disease (CKD). In addition to nitrogen waste products, many pathological biochemical processes also play a role in vascular calcification in chronic kidney damage. Magnesium, a cation vital for the body, may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 105 publications
0
9
0
1
Order By: Relevance
“…While kidney disease can lead to both low and elevated Mg concentrations, our findings indicate that patients with CKD are more likely to develop hypermagnesemia similar to what others have reported [ 6 ]. Hypomagnesemia is also common in CKD, especially if the patient is on a diuretic medication [ 20 ]. Mg wasting via dialysis is the main reason for hypomagnesemia in end-stage renal disease [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While kidney disease can lead to both low and elevated Mg concentrations, our findings indicate that patients with CKD are more likely to develop hypermagnesemia similar to what others have reported [ 6 ]. Hypomagnesemia is also common in CKD, especially if the patient is on a diuretic medication [ 20 ]. Mg wasting via dialysis is the main reason for hypomagnesemia in end-stage renal disease [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypomagnesemia is also common in CKD, especially if the patient is on a diuretic medication [ 20 ]. Mg wasting via dialysis is the main reason for hypomagnesemia in end-stage renal disease [ 20 ]. Mg supplement was found to have a protective effect in dialysis-dependent patients, and Sakaguchi et al documented that hypermagnesemia had a survival benefit in ESRD patients on hemodialysis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above, secondary hyperparathyoidism is one of the main causes of EPO resistance in HD patients, the review by Petho et al. [ 5 ] showed that a significant negative correlation between serum magnesium and intact parathyroid hormone(PTH) in ESKD patients, as well as oral magnesium supplementation alone in HD patients improved chronic kidney disease-mineral bone disease by modulating serum Ca and PTH metabolism.…”
Section: Dear Editormentioning
confidence: 99%
“…The correlation between renal magnesium loss and extensive coronary and vascular calcifications has been firmly established because of the genetic mutation 17q12 [ 24 ]. We recently published a narrative review of the connection between hypomagnesemia and cardiovascular disease [ 25 ]. In our study, we noted that a lack of magnesium was closely correlated with general atherosclerosis.…”
Section: Hypomagnesemia and Cardiovascular Mortalitymentioning
confidence: 99%